N6-Adenosine Methylation in RNA and a Reduced m3G/TMG Level in Non-Coding RNAs Appear at Microirradiation-Induced DNA Lesions - Svobodová Kovaříková, Alena; Stixová, Lenka; Kovařík, Aleš; Komůrková, Denisa; Legartová, Soňa; Fagherazzi, Paolo; Bártová, Eva (Cells, 2020)
The DNA damage response is mediated by both DNA repair proteins and epigenetic markers. Here, we observe that N6-methyladenosine (m6A), a mark of the epitranscriptome, was common in RNAs accumulated at UV-damaged chromatin; however, inhibitors of RNA polymerases I and II did not affect the m6A RNA level at the irradiated genomic regions. After genome injury, m6A RNAs either diffused to the damaged chromatin or appeared at the lesions enzymatically. DNA damage did not change the levels of METTL3 and METTL14 methyltransferases. In a subset of irradiated cells, only the METTL16 enzyme, responsible for m6A in non-coding RNAs as well as for splicing regulation, was recruited to microirradiated sites. Importantly, the levels of the studied splicing factors were not changed by UVA light. Overall, if the appearance of m6A RNAs at DNA lesions is regulated enzymatically, this process must be mediated via the coregulatory function of METTL-like enzymes. This event is additionally accompanied by radiation-induced depletion of 2,2,7-methylguanosine (m3G/TMG) in RNA. Moreover, UV-irradiation also decreases the global cellular level of N1-methyladenosine (m1A) in RNAs. Based on these results, we prefer a model in which m6A RNAs rapidly respond to radiation-induced stress and diffuse to the damaged sites. The level of both (m1A) RNAs and m3G/TMG in RNAs is reduced as a consequence of DNA damage, recognized by the nucleotide excision repair mechanism.
Keywords: metylace; Animals; Stress, Physiological; DNA Damage; Adenosine; Cell Line, Tumor; Guanosine; Genomic Instability; guanosin; RNA, Untranslated; Chromatin; adenosin; Mice; Ultraviolet Rays; RNA; metylace DNA; myši; fyziologický stres; nekódující RNA; Methylation; poškození DNA; chromatin; DNA Methylation; nestabilita genomu; demetylace DNA; zvířata; nádorové buněčné linie; DNA Demethylation; ultrafialové záření